Forest Genetics in Tamil Nadu - Jagannadha Rao, N. (Indian Forester, 1992)
To reduce pressure on natural forests, it has become necessary to increase productivity of high yield plantations, raised from genetically improved seed for maximum output. Therefore, the extensive field studies and intensive research work is to be undertaken. The studies conducted on tree improvement work in Tamil Nadu are given in this paper.